A Diagnostic Overview of Geriatric Oral Cavity in Randegansari, Gresik - Nurfitri Amaliah; Danella Yustiono; R. P. Arief Rakhman (Universitas Ibn Khaldun, 2026)
As the global population ages, the intersection of systemic health, polypharmacy, and oral pathology presents a growing challenge for geriatric care. In elderly populations, oral health is often a reflection of systemic well-being, where chronic diseases and their pharmacological treatments directly modify the oral environment. This study aimed to provide a diagnostic overview of the oral health status—specifically dental caries experience and oral mucosal lesions—among a geriatric and pre-geriatric cohort in Randegansari, Gresik. A descriptive cross-sectional study was conducted involving 35 respondents (62.9% female; 37.1% male). Clinical examinations were performed to determine the Decayed, Missing, and Filled Teeth (DMF-T) index and to identify Oral Mucosal Lesions (OMLs). Systemic health history and routine medication use were also recorded to contextualize clinical findings. The mean DMF-T score for the population was 6.86, categorized as